Manufacturing Engineering Select Proceedings of CPIE 2018 - Sharma, Vishal S.; Dixit, Uday S.; Alba-Baena, Noe.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents selected proceedings of the International Conference on Production and Industrial Engineering (CPIE) 2018. Focusing on recent developments in the field of production and manufacturing engineering, it provides solutions to wide-ranging contemporary problems in manufacturing engineering and other allied areas using analytical models and the latest numerical approaches. The topics covered in this book include conventional and non conventional machining, casting, welding, materials and processing. As such it is useful to academics, researchers and practitioners working in the field of manufacturing and production engineering.
A Variable Viscosity Approach for the Analysis of Static and Dynamic Performance Parameters of Three-Lobe Fluid Film Bering Operating with Tio2 Based Nanolubricant.-Friction stir welding of shipbuilding grade DH36 steel -- Experimental investigation on the effect of cryogenic co2 cooling in end milling of aluminium alloy -- Transient thermal analysis of CO2 laser welding of AISI 304 stainless steel thin plates -- Transient Thermal Analysis On Friction Stir Welding Of AA6061 -- Recycling Of H30 Aluminium Alloy Swarfs Through Gravity Die Casting Process -- Effect on Mechanical and Metallurgical Property of Cryogenic Treated Material SS316 -- Microstructure And Mechanical Properties Of Lamellar TI-6AL-4V Eli Alloy -- Influence Of Process Parameters On Surface Roughness Hole Diameter Error And Burr Height In Drilling Of 304l Stainless Steel -- Investigation Of Impression Creep Deformation Behaviour Of Boron Modified P91 Steel By High End Characterization Techniques -- Tribological and Machining Performance of Graphite, CaF2 and MoS2 Coated Mechanical Micro-Textured Self-Lubricating Cutting Tool -- Chemical Assisted USM Of Acrylic Heat Resistant (BS-476) Glass -- Study Of Temperature Distribution During Fsw Of Aviation Grade AA6082.
Keywords: Manufactures; Computer-aided engineering; Control engineering; Robotics; Automation; Machines, Tools, Processes; Computer-Aided Engineering (CAD, CAE) and Design; Control, Robotics, Automation